Assessment of the water quality in a large reservoir in semiarid region of Brazil - Fernando B. Lopes; Eunice M. de Andrade; Ana C. M. Meireles; Helena Becker; Adriana A. Batista (Revista Brasileira de Engenharia Agrícola e Ambiental)
The aim of this study was to identify spatial and temporal variations in water quality of Orós reservoir, Ceará, Brazil, as well as the sources of contamination. To get this information the Principal Component Analysis (PCA) and Cluster Analysis (CA) was used. Water samples were collected at seven (geo-referenced) points, from April 2008 to March 2011, totalling 4,032 samples. The following attributes of the waters were analysed: temperature, pH, CE, Ca2+, Mg2+, Na+, K+, Cl-, HCO3-, SO4--, turbidity, colour, Sechi transparency, TS, TVS, TFS, TSS, VSS, FSS, TDS, DO, BO5D, total phosphorus, soluble orthophosphate, EC, TTC, total ammonia, TKN, nitrate, SAR and chlorophyll-a. The PCA promoted the reduction from the 32 initial variables to 14, accounting for 84.39% of the total variance. The major factors responsible for water quality composition are: the natural weathering of geological soil components; the entrainment of suspended solids through surface runoff from agricultural areas; and anthropogenic action in the Upper Jaguaribe basin in Ceará. The similarity of the water of the Orós reservoir allows a reduction in the number of sampling points, which may result in significant cost savings without sacrificing the water quality monitoring. The similarity of the waters was influenced by anthropic activities being carried out near the reservoir and all along the watershed.